2022
DOI: 10.3390/atmos13050784
|View full text |Cite
|
Sign up to set email alerts
|

Particle Sedimentation in Numerical Modelling: A Case Study from the Puyehue-Cordón Caulle 2011 Eruption with the PLUME-MoM/HYSPLIT Models

Abstract: Numerical modelling of tephra fallout is a fast-developing research area in volcanology. Several models are currently available both to forecast the dispersion of volcanic particles in the atmosphere and to calculate the particles deposited at different locations on the ground. Data from these simulations can then be used both to manage volcanic crises (e.g., protect air traffic) or perform long-term hazard assessment studies (e.g., through hazard maps). Given the importance of these tasks, it is important tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…More generally in volcanic plumes and spreading umbrella clouds, enhanced (or hindered) settling can cause deposits with mass per unit area larger (or smaller) and grain sizes smaller (or larger) than expected for single size particles (Freret-Lorgeril et al, 2020;Gilchrist & Jellinek, 2021;Tadini et al, 2020Tadini et al, , 2022. Clustering in mixtures containing particles with Stokes number O(1) is an alternative to ash aggregation commonly assumed in simulations to explain enhanced settling (e.g., Tadini et al, 2022). The fact that bimodal fallout deposits, such as the one at Llaima (Figure 8), are relatively rare suggests effective particle size segregation occurs near the vent in most cases.…”
Section: Geophysical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…More generally in volcanic plumes and spreading umbrella clouds, enhanced (or hindered) settling can cause deposits with mass per unit area larger (or smaller) and grain sizes smaller (or larger) than expected for single size particles (Freret-Lorgeril et al, 2020;Gilchrist & Jellinek, 2021;Tadini et al, 2020Tadini et al, , 2022. Clustering in mixtures containing particles with Stokes number O(1) is an alternative to ash aggregation commonly assumed in simulations to explain enhanced settling (e.g., Tadini et al, 2022). The fact that bimodal fallout deposits, such as the one at Llaima (Figure 8), are relatively rare suggests effective particle size segregation occurs near the vent in most cases.…”
Section: Geophysical Implicationsmentioning
confidence: 99%
“…Experimental and numerical studies revealed that the particle settling velocity may increase (Dey et al., 2019; Wang & Maxey, 1993) or decrease (Dey et al., 2019; Fornari et al., 2016; Nielsen, 1993) depending on the degree of turbulence, and it can be lower (Marchetti et al., 2022) or higher (Del Bello et al., 2017) than predicted theoretically for a single particle depending on the particle size, shape, and concentration. Actual particle settling velocities different from theoretical velocities used in models may be a cause of discrepancies between observed and simulated volcanic fall deposits (Tadini et al., 2020, 2022) and this issue is critical in the context of hazard assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation